Diagnosing Recently Defined and Uncommon Salivary Gland Lesions in Limited Cellularity Specimens: Cytomorphology and Ancillary Studies. Issue 5 (September 2020) - Rossi, Esther Diana; Baloch, Zubair; Faquin, William; Pantanowitz, Liron
Abstract : Abstract: Fine-needle aspiration (FNA) has proven to be an essential step in the preoperative evaluation of patients with salivary gland lesions. The diagnosis rendered on FNA specimens helps streamline clinical and/or surgical management. However, despite its usefulness, FNA has known limitations. Fine-needle aspiration may fail to provide a specific diagnosis in some cases because of limited aspirated material, cellular makeup, and/or morphologic heterogeneity. The field of salivary gland pathology is rapidly changing because of the identification of new entities and reclassification of existing lesions based on morphologic features and emerging antigenic and molecular profiles. A management-based cytological diagnosis of these newly reclassified and/or uncommon neoplasms is possible using characteristic morphologic features and specific translocations. Herein, we review the salient morphologic features, immunohistochemistry, and molecular profile of several recently described salivary gland neoplasms in light of clinical management.